2019
DOI: 10.1111/ane.13135
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction after acute ischaemic stroke: Incidence, mortality and risk factors

Abstract: Objectives:To determine the risk factor profiles associated with post-acute ischaemic stroke (AIS) myocardial infarction (MI) over long-term follow-up.Methods: This observational study includes prospectively identified AIS patients (n = 9840) admitted to a UK regional centre between January 2003 and December 2016 (median follow-up: 4.72 years). Predictors of post-stroke MI during follow-up were examined using logistic and Cox regression models for in-hospital and postdischarge events, respectively. MI incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Time to recurrent stroke was constructed using an exponential distribution ( 29 ), while a Gompertz distribution following a previously published study was tested in the sensitivity analysis ( 30 ). Time to MI was constructed using an exponential distribution derived from a registry that prospectively recorded incidence of MI post stroke ( N = 9,840) during the period of 2003–2016 (median follow-up: 4.7 years) ( 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…Time to recurrent stroke was constructed using an exponential distribution ( 29 ), while a Gompertz distribution following a previously published study was tested in the sensitivity analysis ( 30 ). Time to MI was constructed using an exponential distribution derived from a registry that prospectively recorded incidence of MI post stroke ( N = 9,840) during the period of 2003–2016 (median follow-up: 4.7 years) ( 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…Urine: 1: <100mL; 2: ≥100mL and <400mL; 3: ≥400mL and <2500mL; 4: >2500mL. of the association between the hypermagnesemia and high risk of mortality could also be neuromuscular dysfunction, respiratory depression, hypotonia, areflexia, coma and malignant cardiac arrhythmias resulting from hypermagnesemia.- 15,16 In addition, low bicarbonate concentration, reflecting underlying metabolic acidosis, has been proven to cause impaired myocardial contractility, and the expression of inflammatory factors in endothelial cells in animal models. [17][18][19] These mechanisms can cause poor prognosis in AMI patients but still need clinical validation.…”
Section: Discussionmentioning
confidence: 99%
“…And in the Rochester Epidemiology Project, the mean annual incidence of MI was 0.95%. 21 However, in recent multicentre studies conducted in Japan, 4 South Korea 5 and the UK, 6 the risk of MI at 1 year was between 0.09% and 0.54%, which was much lower. Moreover, in nondisabled patients with TIA and minor stroke in TIAregistry.…”
Section: Open Accessmentioning
confidence: 95%
“…3 Given the potential heterogeneity among individual studies existed in systematic review, this result should be cautiously interpreted. Furthermore, several multicentre studies conducted in the UK, Japan and South Korea after 2007 [4][5][6] showed that 1-year incidence of MI after ischaemic stroke decreased to less than 1%, which is more noteworthy.…”
Section: Introductionmentioning
confidence: 99%